(untitled) (Research, Society and Development, 2020)
Introduction: The operating microscope allows for greater magnification, allowing an interpretation of the root canal system and endodontic treatment with greater chances of success, since this specialty requires that the professional work with tactile sensitivity. Objective: Thus, this study aimed to describe the advantages of using the operating microscope in Endodontics. Methodology: it is a narrative review of the literature that uses monographs, dissertations, theses and scientific articles in the thematic area, published in the last 25 years (1995-2020), in Portuguese, English and Spanish, indexed in the BBO databases , SciElo, LILACS, MEDLINE, PubMed and Google Scholar. Results: The studies shown in the microscope favor the illumination of the operational field, allowing to see, with magnification, as internal and deep structures of the root canal system. This expansion was verified in conventional endodontics, making it safer and minimally invasive, favoring the diagnosis of root fractures, in addition to coronary openings free of obstructions, location of root canals, retreatment, perforations and periradicular microsurgery. In addition, promote communication between professionals and between professionals and patients, as well as promoting didactic, pedagogical and marketing purposes. Conclusion: In this way, the operating microscope provides Endodontics with the realization of applications with success rates.